Web Based Sales Information System at Greenvest Source - Abi Surya Wijaya; Aldo Faisal Umam; Arif Rohman Hakim; Maulina Nabila (PT FORMOSA CENDEKIA GLOBAL, 2022)
At this time information technology is experiencing very fast development, along with human needs which also continue to grow, with the internet we will get millions of information, we can even do business selling via the internet. The purpose of this research is to make it easier for buyers and sellers to buy in an easy way by using e-commerce web-based applications. In scientific writing, the research method used by the author is descriptive research methodology. The system design stage is described as designing to build a system and configuring software and hardware components so as to produce a good system, the designed system is one component. The conclusion of this study is to provide information to the general public about the products being sold by presenting pictures and information